Impact of High Hydrostatic Pressure on Physicochemical Characteristics, Nutritional Content and Functional Properties of Cape Gooseberry Pulp (Physalis peruviana L.) - Torres Ossandón, M. J. (2015)
The aim of this research was to assess the effect of high hydrostatic pressure (HHP) treatments (300, 400 and 500MPa/5min) on physicochemical, nutritional and functional properties of Cape gooseberry pulp immediately after processing and after 30 days of refrigerated storage. Results showed that HHP as well as storage time clearly influenced sugars, vitamin C, β-carotene, mineral contents and antioxidant capacity. However, the physicochemical characteristics were not influenced by HHP. Pressurization led to a significant increase in fructose and glucose at 300-500MPa both on day 0 and day 30 (P<0.05). Potassium content increased 8-10% at 300 and 500MPa, while phosphorus content increased 65% compared with control sample at 400MPa at day 0 (P<0.05). The antioxidant activity (2,2-diphenyl-1-picrylhydrazyl) increased after 30 days of storage in pressurized samples at 300 and 500MPa. A maximum antioxidant activity value was observed at 300MPa by means of the oxygen radical absorbance capacity analysis (P<0.05). Practical Applications: Influence of high hydrostatic pressure (HHP) on Cape gooseberry pulp quality was evaluated immediately after processing and after 30 days of storage at 4C. Physicochemical, nutritional and functional properties of the gooseberry pulp were determined. The results of this work may contribute to a better assessment of the benefits of high pressure processed gooseberry pulp. HHP processing preserves and enhances quality of bioactive compounds as well as improves their stability during storage, which may lead to the development of new functional food products with this pulp as basic ingredient.